Reasons for Not Performing Mechanical Thrombectomy: A Population-Based Study of Stroke Codes. Issue 9 (22nd July 2021) - Guisado-Alonso, Daniel; Martínez-Domeño, Alejandro; Prats-Sánchez, Luis; Delgado-Mederos, Raquel; Camps-Renom, Pol; Abilleira, Sònia; de la Ossa, Natalia Pérez; Ramos-Pachón, Anna; Cardona, Pere; Rodríguez-Campello, Ana; Molina, Carlos A.; Rudilosso, Salvatore; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Mechanical thrombectomy (MT) is effective for acute ischemic stroke (AIS) in selected patients with large intracranial vessel occlusion. A minority of patients with AIS receive MT. We aimed to describe the reasons for excluding patients with AIS for MT. Methods: We evaluated patients with AIS in a prospective population-based multicenter registry (Codi Ictus Catalunya registry) that includes all stroke code activations from January to June 2018 in Catalonia, Spain. We analyzed the major reasons for not treating with MT. Results: Stroke code was activated in 3060 patients. Excluding 355 intracranial hemorrhages and 502 stroke mimics, resulted in 2203 patients with AIS (mean age 72.8±13.8 years; 44.6% were women). Of the patients with AIS, 405 (18.4%) were treated with MT. We analyzed the reasons for not treating with MT. The following reasons were considered not modifiable: absence of large intracranial vessel occlusion (922, 41.9%), transient ischemic attack (206, 9.4%), and more than one cause (124, 5.6%). The potentially modifiable reasons for not performing MT by changing selection criteria were as follows: an intracranial artery occlusion that was considered inaccessible or not indicated (48, 2.2%); clinical presentation that was considered too mild to be treated (222, 10.1%); neuroimaging criteria (129, 5.9%), age/prior modified Rankin Scale score/medical comorbidities (129, 5.9%), and therapeutic time window >8 hours (16, 0.7%). Conclusions: In our area, considering all potentially modifiable causes for not performing MT, the percentage of patients with AIS eligible for MT could increase from 18.4% to a maximum of 43.1%. The clinical benefit of this increase is still uncertain and should be confirmed in future trials. Criteria for stroke code activation must be considered for the generalizability of these results.